(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the contribution of women to science, the historical process of recovery, modern development trends and future opportunities. It highlights the progress achieved through women’s activity in scientific fields, gender equality policies, education and innovation. The article provides examples from Uzbekistan and world experience, and also provides suggestions for increasing the potential of women.